Oil Recovery Test Using Bio surfactant of Halo tolerant Bacteria Brevundimonas diminuta and Bhurkholderia glumae at variation of NaCl Salt Concentrations (Indonesian Society for microbiology, 2017)
Oil recovery test has been done by using crude biosurfactant from Brevundimonas diminuta and Bhurkholderia glumae indigenous halo tolerant bacteria with the vatiation of NaCl salt concentration 0; 1.5; 3; 4.5; 6; and 7.5%. Oil recovery test was obtained by determining % TPH (Total Petrolem Hidrocarbon). The sample concentration was 28.19% TPH, it was extracted by using biosurfactant of Brevundimonas diminuta and Bhurkholderia glumae bacteria, the optimal salitnity conditions were at 3, 4.5% salt concentrations with the value oil recovery as much as 50.41, 69.97 % respectively. Oil components which extraction by biosurfactant were analyzed by using GC-MS (Gas Chromatography-Mass Spectrophotometry). The result from analyzes GC-MS could be concluded that bacteria Brevundimonas diminuta could dissolve hydrocarbon compounds short chain carbon atom at fraction <C10–C14 and long chain carbon atom at fraction >C22. <C10, C11-C14dan C15-C17 and Bhurkholderia glumae could dissolve hydrocarbon compounds short chain carbon atom at fraction <C10–C14 and long chain carbon atom at fraction >C22 according to the retention time.